Simulation of Virtual MIMO Base Stations for Mobile Location in IMT-Advanced Networks - Awang Md Isa, Azmi; Mohamad Isa, Mohd Sa'ari; Zakaria, Zahriladha; Mohd Zin, Mohd Shahril Izuan (2012)
The conventional Location and Positioning (L&P) methods rely on availability of base station (BS) locations as well as mitigation of propagation effects. It is known that the location estimation accuracy suffers from poor geometric dilution of precision (GDOP) caused by BS location as the conventional location algorithms which result in large GDOP values correspond to poor geometrical topology. In addition, NLOS effects cause a large error in time of arrival (TOA) reading; thus affecting mobile station (MS) estimation accuracy. In this paper a novel concept of virtual BS (VirBS) utilizing multiple input multiple output (MIMO) technology has been introduced and applied for improving L&P accuracy. The performance of the proposed algorithm has been evaluated via computer simulations. The simulation results demonstrate that the proposed algorithm allows up to 30 percent improvement in L&P accuracy without additional expenditure on network architecture.